Changes in yield and nutritive value of red clover (Trifolium pratense L.) and Festulolium (Festulolium braunii (K. Richt) A. Camus) under drought stress - Staniak, Mariola (Agricultural and food science, 2019)
The aim of the research was to assess the impact of water stress on the yield and content of basic nutrients in the biomass of Trifolium pratense and Festulolium braunii cultivated in pure stand and in mixture. A pot experiment was carried out in 2012–2014, at two levels of soil moisture: well-watered and drought stress. The study showed that stress significantly reduced the dry matter yield (DMY), the most in T. pratense, followed by mixture, and F. braunii. The effect of drought stress on the nutritive value was considerable less pronounced than the influence on DMY. No significant influence of water deficit on crude protein, crude fibre and crude ash contents was found, but only on water-soluble carbohydrate and crude fat content in one year of the study. It was found, that under drought stress T. pratense is more suitable for cultivation in the mixture with F. braunii than in pure stand, due to a lower reduction of DMY and no adverse effect of water deficiency on yield quality.